What if Hitler had won WWII and met Kennedy in 1964? Perception and evaluation of counterfactual historical fiction - Kakimova, Ainur; Salgaro, Massimo (Frontiers in Human Neuroscience, 2024)
Introduction This study investigates the cognitive processing and perception of counterfactual historical fiction and its effects on readers' receptivity to fascism, superstitious beliefs, and satisfaction with the present state of politics. Counterfactual historical fiction presents alternative realities where history diverges from the official historiography, such as in Robert Harris' novel Fatherland, which depicts a counterfactual world where Hitler won WWII. It was hypothesized that reading this genre incurs additional cognitive costs and is perceived with less realism and more aesthetic appreciation compared to historical fiction. Methods Seventy-four subjects were divided into two groups and presented with two versions of paragraphs from Fatherland. An experimental group read the original version, describing a counterfactual reality where Hitler is still alive in 1964 (counterfactual historical fiction). A control group read a manipulated version, where events are made plausible by being backdated to 1941 (historical fiction). The study employed a triangulation of methods, utilizing online eye tracking and self-report questionnaires with 7-point Likert scale measurements. Results The results indicate that counterfactual historical fiction is associated with increased cognitive demands at the first point of divergence, i.e., the first linguistic cue indicating counterfactuality. This genre also induced less perceived realism of history (factuality) and more surprise. Both versions of the text impacted readers by decreasing agreement with fascism, reducing superstitious beliefs, and enhancing their positive evaluation of the current political situation. Discussion The study reveals the cognitive processing of counterfactual historical fiction, highlighting the need for revising current theoretical assumptions. Additionally, the positive impact on readers' attitudes and beliefs may underscore literature's potential role in fostering critical thinking, pro-social behavior, and satisfaction. Further research is suggested for subsequent empirical validation.